The Narrative Form in Leonid Yuzefovich’s Novel “Cranes and Dwarfs” - Makarova, Viktorija; Petrovska, Justyna (Verbum, 2021)
The paper is devoted to the features of the narrative form of Leonid Yuzefovich’s novel “Cranes and dwarfs”. The authors of the paper focuses on the lexical and grammatical tools that allowed the author of the novel to introduce different types of a narrator into the text. Examples illustrating that in the text of the novel under analysis the speaker and the beholder do not always match: 641 examples were related to varieties of free indirect speech. The following types of the free indirect speech constructions were analysed: when the subject of speech and the subject of consciousness differ in such cases: 1) indication of the spatial or temporal localization of the character; 2) an indication of the physical or intellectual perception of the situation (or object, or natural phenomena); 3) broadcast of the character’s thoughts; 4) description of the character’s emotions; 5) nomination of relatives and body parts of the character. As well as a list of lexical-grammatical markers of the modernist narrative form of the novel "Cranes and dwarfs" are provided in the report.